Analysis of Accounting Information Systems and Operational Budgets as An Internal Control Tool for Lending - Pinnaringtyas, Septiana Wahyu; Isharijadi, Isharijadi; Whartanti, Liana Vivin (Economic Education Analysis Journal, 2021)
This study aimed to determine the Analysis of Accounting Information Systems and Operational Budget as a Tool for Internal Control of Credit Distribution at PT Bank Perkreditan Rakyat (BPR) Buana Citra Sejahtera Magetan. The research was conducted on: 1 director, 1 IT officer, and 1 operational member of PT Bank Perkreditan Rakyat (BPR) Buana Citra Sejahtera Magetan. The research was conducted at PT Bank Perkreditan Rakyat (BPR) Buana Citra Sejahtera Magetan. The research method used was a qualitative method with descriptive study research type. Collecting data used observation, interviews, documentation, and triangulation. The results showed that the internal control of credit distribution was related to the accounting information system run by PT. Buana Citra Sejahtera People's Credit Bank (BPR). Internal control of credit distribution was related to the operational budget carried out by PT. Buana Citra Sejahtera People's Credit Bank (BPR).